A Subtitling Analysis On Directive Utterance In Homefront Movie By Baba Naheel - Kusuma, Rendy Edo Perdana; , Dr.Anam Sutopo,M.Hum (2016)
This research aims to identify the method used for subtitling on directive utterance, to classify the kind of directive utterance used, and to describe the accuracy of subtitling on directive utterance in Homefront movie by Baba Naheel. The research type is the qualitative research. The object of the study in this research is directive utterance in the Homefront Movie and its subtitle by Baba Naheel. Data is divided into primary data consists of data collected from Homefront Movie and its subtitle in English and Indonesian, then secondary data is from the books, internet, research paper, dictionary, and other sources related to the study. Data source is from the cassette disk of "Homefront" movie that released at 2013. Technique of collecting data consists of four steps such as (1) watching Homefront movie and its subtitle, (2) taking notes of the subtitle, (3) collecting the data which includes into directive utterance, and (4) coding the data. Technique of analyzing data consists of four steps such as (1) analyzing the method used in the making subtitle of data, (2) classifying the kinds of directive utterance of data which are command, suggestion, request, and warning, (3) analyzing the accurateness of subtitling on Homefront movie, and (4) making conclusion and suggestion. The results of the research are: (1) the methods used for subtitling on directive utterance are three methods type in which are 23 data or 46 % using the communicative translation method, 21 data or 42 % using the idiomatic translation method, 6 data or 12 % using free translation method, (2) the kinds of directive utterance used are four kinds in which are 16 data or 32 % as commanding category, 20 data or 40 % as requesting category, 8 data or 16 % as suggesting category, and 6 data or 12 % as warning category, and (3) the accuracy of subtitling on directive utterance has three criteria in which are 31 data or 62 % which categorized into very accurate criteria, 12 data or 24 % which categorized into less accurate criteria, and 7 data or 14 % which categorized into not accurate criteria.